BRAND IMAGE MEMEDIASI HUBUNGAN E-COMMERCE DENGAN KEPUTUSAN PEMBELIAN KONSUMEN - Pratiwi, Ni Kadek Anggi; Ekawati, Ni Wayan (E-Jurnal Manajemen; Vol 9 No 6 (2020)DO - 10.24843/EJMUNUD.2020.v09.i06.p11, 2020)
The development of tourism in Bali is growing more rapidly so that the competition of lodging service providers is also getting tougher. Purpose of this study is to explain the effect of e-commerce on purchasing decisions, e-commerce on brand image, brand image on purchasing decisions, and the role of brand image mediating the relationship of e-commerce with purchasing decisions. This research was conducted on THE HAVEN Bali Seminyak hotel customers who book hotel rooms using the hotel's official website. 136 people are used as respondents with  purposive sampling method and analyzed using path analysis. The results found that e-commerce had  positive and significant effect on brand image. This study also found that each variable, e-commerce and brand image significantly had positive effect on purchasing decisions, in addition to that brand image also significantly mediated the relationship of e-commerce to purchasing decisions. Keywords: e-commerce, brand image, purchase decision